2006
DOI: 10.1007/s11292-006-9019-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of drug court effects on recidivism

Abstract: Drug courts have been proposed as a solution to the increasing numbers of drug involved offenders entering our criminal justice system, and they have become widespread since their introduction in 1989. Evaluations of these programs have led to mixed results. Using meta-analytic methods, we systematically reviewed the extant evidence on the effectiveness of drug courts in reducing future criminal offending. Fifty studies representing 55 evaluations were identified, including both experimental and quasi-experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
279
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(289 citation statements)
references
References 39 publications
(38 reference statements)
8
279
0
2
Order By: Relevance
“…This assertion echoes the general consensus in the drug and alcohol treatment field based on metaanalyses of so-called "drug courts": coerced treatment is more effective in terms of compliance and outcomes than voluntary treatment (e.g., Wilson, Mitchell, & MacKenzie, 2006). As discussed in the section above on "Implementation," the question remains about how to establish a consistent and integrated referral system in an efficient and cost effective manner.…”
Section: Discussionmentioning
confidence: 75%
“…This assertion echoes the general consensus in the drug and alcohol treatment field based on metaanalyses of so-called "drug courts": coerced treatment is more effective in terms of compliance and outcomes than voluntary treatment (e.g., Wilson, Mitchell, & MacKenzie, 2006). As discussed in the section above on "Implementation," the question remains about how to establish a consistent and integrated referral system in an efficient and cost effective manner.…”
Section: Discussionmentioning
confidence: 75%
“…Yet in addition to these studies, empirical evaluations have also been undertaken to assess the external impact of similarly functioning specialty courts that operate within the judicial system. A systematic review of the research evidence has even been conducted on the societal impact of at least one type of these judicial organs (Wilson et al, 2006). Indeed, methodologically, there may be much to learn from external impact evaluations of specialist courts in the judicial sector (Plotnikoff and Woolfson, 2005).…”
Section: Reasons For Optimismmentioning
confidence: 99%
“…It concluded that drug courts reduced recidivism during the length of the drug court program but that evidence was mixed on whether it affected outcomes after the program ended. The GAO bemoaned the state of drug court evaluations for In one meta-analysis, other researchers found evidence, but tentative evidence given weak research design, for positive post-program effects on recidivism (Wilson, Mitchell, & MacKenzie, 2006).…”
Section: Replication and Institutionalizationmentioning
confidence: 99%